Pengaruh Penggunaan Bahan Ajar Leaflet Geografi Terhadap Hasil Belajar Siswa SMA NU Genteng Banyuwangi - M. Rizqon Al Musafiri (heritage, 2021)
Abstract The results of observations on students of class XI IPS 1 and XI IPS 2 at SMA NU Genteng Banyuwangi are still below the minimum completeness score of 75 as many as 35 students. researchers use leaflet teaching materials supplements to improve student learning outcomes. This research was conducted in January 2020 at SMA NU Genteng. The population and sample in this study were students of class XI IPS 1 and XI IPS 2 with the control class selected using cluster random sampling technique. The data used are quantitative to calculate the N-gain value from the difference between the pretest and posttest scores. The data were analyzed using t test and Mann Whitney-U. The increase in student learning outcomes is indicated by the difference in the average pretest score of 63.6 and posttest of 84.6. The average value is in accordance with the minimum completeness set by the school, which is 75. In addition, it is also supported by an N-Gain value of 83.2 which shows an increase in student learning outcomes before and after learning is carried out. The percentage of students who dare to express their opinions is 72.9%, students who are active in group work are 78.6%, who are actively asking questions are 76.4%, dare to present the results of discussions are 81.6% and exchange information are 75.7% . These indicators show the improvement experienced by students. Students who experienced an increase in aspects of knowledge (C1), aspects of understanding (C2) and aspects of analyzing had an average N-gain of 71.2.